Strategies for Developing Waqf Land in Kelantan, Malaysia - Mohamad Sayoti, Nur Saidatul Izyan; Omar, Abdul Jalil (Research in Management of Technology and Business, 2025)
Waqf refers to a permanent voluntary division of property that cannot be overturned by another party under Sharia law. Waqf is part of the Muslim community's required worship. Waqf also plays an important role in solving Malaysian society's problems, such as reducing poverty, providing health facilities, and education centers, and building orphanages, mosques, business centers, and shelters for the needy. Even though waqf has been around for a long time, its development and progress are still considered inadequate. In Malaysia, religious institutions operate independently and are managed and administered in each state. In addition, the Islamic Religious Council of State (MAIN) serves as an administrator for the waqf. The Kelantan Islamic Religious Council (MAIK) conducted this study to identify waqf land development strategies in Kelantan. An interview with waqf management officers from the Kelantan Islamic Religious Council (MAIK) was conducted to achieve the goals of this research. It is hoped that this study could produce some positive results on the waqf land development strategy in the state of Kelantan. Several development strategies are proposed in this paper to address some factors related to the development of waqf land and fully utilize it for the community's economic progress.